AZAN MAGAZINE AS A SPREADING MEDIA ISLAMIC KNOWLEDGE IN PATANI - Suraiya Chapakiya (Proceeding International Seminar of Islamic Studies, 2023)
Efforts to awaken humanity is not an easy endeavor. He requires seriousness and unified commitment at all levels and layers of society, especially those with the title of clergy and leaders. Scholars and leaders must be held accountable for the good and bad of something society and the ups and downs of a civilization. Rasulullah SAW said: "Two classes of people, when they are damaged, all humans are damaged, if they are good then all humans are good. They're meant to be namely the scholars and umara' (scientists and leaders)". Therefore, Islam and progress are synonymous. Progress must be made in a unified way between spiritual, intellectual, emotional and material strength. Religion and nation will become strong, great, brilliant, resplendent and spellbinding when his people reach the glorious stage of all aspects. This matter due to the downfall of a civilization including Islamic civilization appeared at one time in the past was due to his people being passive, uncivilized, uneducated, dayus, untrustworthy and irresponsible. Therefore, awareness and desire to become a developed nation is necessary polished again so that its sheen can shine and be enjoyed by all nation in the world.